Mediating Effects of Protective Factors on COVID-19 Anxiety and Academic Performance of K to 12 Filipino Learners: A PLS-SEM Analysis with WarpPLS - Kevin D. Caratiquit (Journal of Social, Humanity, and Education, 2022)
Purpose: This study investigates the interrelationship among COVID-19 anxiety, mindfulness, COVID-19 information avoidance, preventive behavior, and academic performance. Methodology: The study assessed protective factors as mediators of COVID-19 anxiety and academic performance using WarpPLS. The study participants were K-12 Filipino students from a secondary school in Cagayan, Philippines, identified through convenience sampling. Results: COVID-19 anxiety, mindfulness, information avoidance, and preventive behavior were found to be negatively correlated. Preventive behavior is associated with improved academic performance. Conversely, there was a negative correlation between mindfulness, COVID-19 information avoidance and academic performance. The association between COVID-19 anxiety and academic achievement is only mediated by mindfulness and preventive behavior. Conclusions: Mindfulness and preventive behavior mediate the effect of COVID-19 anxiety on students’ academic performance, helping to reduce stress and support learning. Limitations: Preventive factors that may affect COVID-19 anxiety and academic achievement are only considered. Also, the participants are limited from a secondary school in Cagayan, Philippines. Contributions: With the pandemic having a substantial influence on the municipality, the study would be helpful to manage and control the effect of the outbreak on the academic performance of the learners.